Economic technology analysis of LTE advanced pro dual spectrum licensed and unlicensed access using discounted cash flow methods - Setiyo Budiyanto; Erman Al Hakim; Fajar Rahayu (Institute of Advanced Engineering and Science, 2021)
Since implementing the long term evolution (LTE) technology, the surge in data service traffic has increased, causing an increase in demand spectrum, which has resulted in gaps in capacity requirements. Wireless service providers can respond to LTE technology updates. With LTE advanced pro technology that utilizes unlicensed spectrum technology can provide solutions to increase capacity and throughput. In this study, LTE advanced pro planning by capacity method to find the number of eNodeB and using the discounted cash flow method to analyze the feasibility of the costs to be invested in the implementation of the LTE. The results of the four simulated scenarios concluded that the number of eNodeB from the IV scenario with 20 MHz bandwidth at 1800 MHz frequency and 20 MHz bandwidth at 5 GHz frequency amounted to 23 sites, with a positive NPV value of 271,936.96, IRR of 14.91%, and for payback period occurred in the 3rd year. Thus the fourth scenario is feasible to be implemented.